PENGEMBANGAN KAPASITAS PEREMPUAN BAGI IBU-IBU RELAWAN PROGRAM PALIATIF DI DESA KAMBINGAN DAN DESA KREMBUNG, KECAMATAN CERME, KABUPATEN GRESIK - Sulikah Asmorowati; Inge Dhamanty (Universitas Airlangga, 2020)
The high rate of deaths caused by serious illnesses has led the World Health Organization (WHO) to recommend palliative care that is considered to be able to improve the quality of patient’s live Palliative care or service is service for patients with serious illnesses, such as cancer (stadium or end-stage). In this activity, however, palliative care and service is extended so that it includes diseases that are not contagious but deadly (thus, contributed significantly to mortality rate), including such illnesses as diabetes, high-blood pressure, cholesterol, stroke and other similar illnesses. These illnesses are now increasingly being suffered by and become the major cause of death (caused by illnesses) amongst Indonesians. In order to increase the availability of palliative services in the target area, this community project provides training and assistance to develop women’s capacity in the villages of Kambingan and Ngembung, Cerme, Gresik, so that they are ready to volunteers for palliative care and service in their respective communities. The projects were conducted by providing material through lectures, and modules; followed by assistance to form a team of palliative case and service. At the end, this project resulted in the increasing understanding, and capacity of women (and mothers or PKK member), as the target groups about palliative care and services. In turn, the women were then ready to become volunteers for palliative care and program.abstrakTingginya tingkat kematian akibat penyakit serius membuat WHO menyarankan untuk melakukan perawatan paliatif yang dianggap dapat meningkatkan kualitas hidup pasien. Program atau layanan paliatif adalah pelayanan kepada pasien dengan penyakit berat, yaitu kanker (stadium akhir). Dalam kegiatan pengabdian masyarakat (pengmas) ini, layanan paliatif diperluas sehingga meliputi pula penyakit-penyakit yang tidak menular namun mematikan, seperti penyakit diabates, darah tinggi, kolesterol, stroke dan sejenisnya yang dewasa ini semakin banyak di derita masyarakat Indonesia. Kegiatan pengmas ini memberikan pelatihan dan pendampingan untuk mengembangkan kapasitas ibu-ibu tim penggerak dan anggota PKK di Desa Kambingan dan Desa Ngembung, Kecamatan Cerme, Kabupaten Gresik agar siap untuk menjadi relawan program paliatif di lingkungan masyarakat masing-masing. Metode yang digunakan dalam kegiatan ini adalah dengan pemberian materi melalui ceramah, pemberian modul, serta pendampingan pembentukan tim paliatif sebagai follow-up kegiatan. Hasil yang dicapai dari kegiatan pengabdian masyarakat ini adalah meningkatnya pemahaman masyarakat khususnya ibu-ibu tentang layanan paliatif, serta meningkatnya kapasitas mereka,sehingga siap menjadi relawan program paliatif.